2022
DOI: 10.3390/medicina58050632
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Maternal Periodontitis and Preterm Birth: A Case-Control Study in a Low-Resource Setting in Sudan, Africa

Abstract: Background and Objectives: Vast data have been published recently on the association between periodontitis and preterm birth (PB). However, these studies have shown inconsistent results. Few of them were conducted in Africa, and data has not been published on the association between periodontitis and PB in Sudan. Materials and Methods: A case-control study was conducted at the Omdurman maternity hospital in Sudan from February through October 2021. The cases were women with spontaneous PB (<37 weeks), and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The study stated that women with periodontitis had a two-fold greater chance of delivering preterm babies than women who had no periodontitis (odds ratio = 2.05). 24 A retrospective unmatched case‒control study in Rwanda concluded that women with periodontitis had six-fold higher chances of premature delivery than periodontally healthy women (odds ratio: 6.360). 25 In 2020, a hospital-based cross-sectional study using postpartum full-mouth periodontal examination reported that women with severe periodontitis had 3.46-fold higher odds of preterm births than non-periodontitis pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…The study stated that women with periodontitis had a two-fold greater chance of delivering preterm babies than women who had no periodontitis (odds ratio = 2.05). 24 A retrospective unmatched case‒control study in Rwanda concluded that women with periodontitis had six-fold higher chances of premature delivery than periodontally healthy women (odds ratio: 6.360). 25 In 2020, a hospital-based cross-sectional study using postpartum full-mouth periodontal examination reported that women with severe periodontitis had 3.46-fold higher odds of preterm births than non-periodontitis pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study in Africa assessed the association between periodontitis and preterm births using the Community Periodontal Index. The study stated that women with periodontitis had a 2X greater chance of delivering preterm babies than women who had no periodontitis (odds ratio = 2.05) (24). A retrospective unmatched casecontrol study in Rwanda concluded that women with periodontitis had 6X more chances of premature delivery than periodontally healthy women (odds ratio: 6.360) (25).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Kenya reported that women with periodontitis have 2 times risk of giving birth to preterm babies than women without periodontitis. 12 In Ethiopia, a study reported 2-4 times the odds of giving birth to preterm babies in women with periodontitis 13 while in Rwanda is six-fold risk of preterm in women with periodontitis than those with no periodontitis. 14 A recent study in Rwanda showed a high prevalence of periodontitis (60.5%) among pregnant women and a six-fold risk of preterm deliveries in women who had periodontitis.…”
Section: Policy Outcomes and Implicationsmentioning
confidence: 99%